The implementation of Building Information Modelling (BIM) in Malaysian construction industry / Muhammad Aizzat Mohd Noor and Nor Amin Mohd Radzuan - Mohd Noor, Muhammad Aizzat; Mohd Radzuan, Nor Amin (2023)
Building Information Modelling (BIM) implementation has received a lot of attention in the Malaysian construction industry. BIM is a digital tool that allows for collaborative work, communication, and data management throughout the project lifecycle. This study explores the current state of BIM adoption in Malaysia, its benefits, challenges, and potential implementation strategies. The research identifies the importance of BIM through a comprehensive review of literature and a questionnaire with industry professionals. The findings emphasise the importance of industry-wide awareness campaigns promoting the benefits of BIM, as well as the implementation of training programmes and workshops aimed at improving BIM knowledge and skills among construction professionals. Furthermore, the study emphasises the importance of government support for BIM adoption through policies, incentives, and regulations. By embracing BIM and implementing the recommended strategies, the Malaysian construction industry can unlock its full potential for increased efficiency, cost savings, and quality improvement.